The financing of small business - Bates, James A. (London : Sweet & Maxwell, 1964)
This book provides an outline of the main sources of funds available to the small firm and the results of the survey undertaken by the Oxford University Institute of Statistics in 1956, of the financial and other problems of small and medium sized manufacturing firms. It covers topics including: the importance of small business; the growing smaller business; financing and small business; financial planning and control; profits and internal finance; long term capital; bank credit; trade credit; other sources of funds; and mergers and takeovers.
Bibliography: p. 216-219.
lje 16/10/18
Loans
Keywords: Small business; Finance; Credit